Mitochondria in reproduction and fertility: mitochondria and gametes 1 - Panloup, Pascale May (Henry Stewart Talks, 2018)
Introduction to the role of mitochondria in embryonic development, Mitochondrial life cycle, dynamics, biogenesis and mitophagy, Mitochondria and gametes: in spermatozoa and spermatogenesis, in oocyte and oogenesis, The bottleneck theory, The importance of mtDNA content in oocyte competence